A New Nonlinear Contraction Principle in Partial Metric Spaces. (7th December 2016) - Zhang, Yi; Zhu, Jiang
Abstract : We present a new nonlinear contraction principle on partial metric spaces and prove the existence of common fixed point. We also give some examples to show our results and apply our results to study the existence of common bounded solution of the system of functional equations.